2010
DOI: 10.1017/s0025315410000950
|View full text |Cite
|
Sign up to set email alerts
|

The population of Errina aspera (Hydrozoa: Stylasteridae) of the Messina Strait (Mediterranean Sea)

Abstract: Errina aspera is the only species belonging to the family Stylasteridae known from the Mediterranean Sea. The distribution of this species includes the Messina Strait, the Gibraltar Strait and the Atlantic coast of Morocco. In spite of the taxonomic and biogeographical importance of this species, no studies were conducted on its population structure in the Messina Strait. Here we report a study carried out with the aid of a ROV on a horizontal transect 350 m long at a depth comprised between 83 and 105 m where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 14 publications
4
30
0
Order By: Relevance
“…Sizefrequency distributions, obtained for the two species in the studied localities, indicate unimodal trends with peaks for the intermediate size classes and long tails. This kind of trend is very common in modular organisms like sponges and corals (Linares et al, 2008;Salvati et al, 2010). We hypothesise that the sponges grow quickly to increase the filtering efficiency and to avoid the sedimentation while their maximal size is probably constrained by the friction with the current (and partially by predation).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Sizefrequency distributions, obtained for the two species in the studied localities, indicate unimodal trends with peaks for the intermediate size classes and long tails. This kind of trend is very common in modular organisms like sponges and corals (Linares et al, 2008;Salvati et al, 2010). We hypothesise that the sponges grow quickly to increase the filtering efficiency and to avoid the sedimentation while their maximal size is probably constrained by the friction with the current (and partially by predation).…”
Section: Discussionmentioning
confidence: 88%
“…Symbiotic relationships between sponges and zoanthids have been frequently observed in tropical and subtropical waters (Swain & Wulff, 2007;Reimer et al, 2008), from shallow to deep habitats (Beaulieu, 2001). In the Mediterranean Sea, it is well documented the recurrent relationship between Parazoanthus axinellae Schmidt, 1862 and several species of sponges belonging to the genus Axinella (Sarà & Vacelet, 1973;Previati et al, 2010), however, some species are more commonly found on hard bottom substrates (Salvati et al, 2010). As pointed out recently (MontenegroGonzález & Acosta, 2010), the sponge morphology is an important trait in zoanthid habitat selection.…”
Section: Discussionmentioning
confidence: 99%
“…Pachylasma giganteum (Philippi, 1836), Strait of Messina to off W. Africa, facultative with Errina aspera (L.), at shelf break, 150–200 m (Darwin 1854, Zibrowius 1981, Fredj and Giermann 1982, Di Geronimo and Fredj 1987, Zibrowius and Cairns 1992, Foster and Buckeridge 1995, Salvati et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…The hydrocoral Errina aspera (Linnaeus, 1767) can also be included in the CWCs sensu lato, because it is an habitat-former species of the mesophotic and the upper aphotic zones, where it can occasionally form monospecific stands showing high densities and being similar to CWC habitats [56].…”
Section: Ecosystem Goods and Services Provided By The Mesophotic And mentioning
confidence: 99%